Development of biomimetic pancreatic cancer 3D in vitro models for preclinical drug screening - Monteiro, Maria Vinhas (2024)
Pancreatic ductal adenocarcinoma (PDAC) is a disease with one of the highest mortality rates and with an increasing incidence worldwide. Currently, clinically administered therapies for the PDAC treatment are still extremely ineffective and of limited access. Given this scenario, it is urgent to investigate and validate new therapies for the treatment of this neoplasia. PDAC is a cancer with a unique stratified bio-architecture and characterized by an exacerbated desmoplastic reaction involving cancer-associated fibroblasts, immune cells and extracellular matrix proteins (ECM), which play a significant role in tumor progression and resistance to the currently used therapies in a clinical setting. The absence of cell-based in vitro models capable of reproducing the PDAC desmoplastic microenvironment and the histo-morphology results in a low correlation between the performance of new therapies in preclinical trials and that observed in controlled clinical trials. In this sense, three-dimensional (3D) in vitro tumor models emerge as a more suitable solution for preclinical evaluation when compared with the most frequently used two-dimensional (2D) cell cultures. 3D models represent more biomimetic models as they allow a more robust and realistic recapitulation of the tumor microenvironment, contributing to the discovery of new biomarkers and to the pre-clinical evaluation of new drugs in a more accurate way. Amongst currently developed 3D in vitro PDAC platforms, few are those that accurately recapitulate cell heterogeneity, tumor architecture and fibrotic stroma. To overcome these limitations, this dissertation focuses on bioengineering and characterization of a new 3D PDAC model, consisting of a biomimetic co-culture of pancreatic cancer cells (PANC-1) and cancer-associated fibroblasts (CAFs). This 3D model demonstrated to recapitulate the cellular components, their spatial distribution and resistance to pharmacological therapies in a similar way to that found in human tumors.